Hadith and Sunnah - Qazi, Mazharul Haq, Dr. (Islamabad Dawah Academy, 1999)
Topical arrangement and English rendering of Hadith (Islamic traditions) by a Pakistani scholar
Keywords: Sunna -- Hadith--Evidences, authority, etc -- Islamic law